Village Fund Management for Clean Water Provision in Warmon Village Community, Bamus Bama District - Maikel Yeblo; A. Sakti R. S. Rakia; Masrifatun Mahmudah; Muhammad Asri; Wakano Abd Kadir (Journal of Law Justice (JLJ), 2024)
The type of research used in this study uses one type of approach, namely a normative juridical approach.  This research was conducted in Warmon Village, Bamus Bama District, Tambrauw Regency. The type of data that researchers obtain is descriptive data. The analysis technique is carried out continuously starting with reviewing all available data from various sources, namely interviews, observations that have been made in field notes, documents and so on until the conclusion is drawn. The results of this study indicate that the implementation of village fund management related to the implementation of the Clean Water Supply program by the Warmon Village government, Bamus Bama District, Tambrauw Regency is in accordance with the Village Fund management law. What are the obstacles in managing village funds for the provision of clean water to the people of Warmon Village, Bamus Bama District, Tambrauw Regency. The evaluation stage is not carried out in the Kubu Kandang Village Government. Lack of understanding of the Village Government regarding the cycle or drilling well system to produce clean water. Lack of community participation in maintaining the cleanliness of the well environment What efforts are made in the management of village funds for the provision of clean water to the people of Warmon Village, Bamus Bama District, Tambrauw Regency. The efforts made by the Village Government in improving the quality of clean water services in Warmon Village are as follows. Establish good cooperation between the Village Government and Community Institutions. Periodic monitoring/control of clean water facilities. Increase community participation.